2020
DOI: 10.1111/eje.12491
|View full text |Cite
|
Sign up to set email alerts
|

National Student Survey: Reliability and prediction of overall satisfaction scores with special reference to UK Dental Schools

Abstract: Introduction The aim of this study was to assess the reliability of the UK National Student Survey (NSS) (2018) and explore the predictive values of individual questions and question domains on the overall satisfaction score. Methods UK NSS result data (for 2018) were assessed for all those providers that award an undergraduate degree in dentistry. To analyse the correlation of each question item to the overall satisfaction question (question 27), a bivariate 2‐tailed Pearson correlation test was conducted, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…However, these ideas cannot explain why we found different results from more recent studies (HEFCE, 2016;Satterthwaite & Vahid Roudsari, 2020). One possible reason for this is that the solution that is found may depend on the way that the analysis is undertaken.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…However, these ideas cannot explain why we found different results from more recent studies (HEFCE, 2016;Satterthwaite & Vahid Roudsari, 2020). One possible reason for this is that the solution that is found may depend on the way that the analysis is undertaken.…”
Section: Discussioncontrasting
confidence: 85%
“…For example, one study found that the NSS questions were reliable when assessing the data from dentistry courses (Satterthwaite & Vahid Roudsari, 2020). Moreover, smaller-scale pilot studies have been undertaken to analyse the structure data at a holistic level across a variety of courses (HEFCE, 2015(HEFCE, , 2016.…”
Section: National Student Survey (Nss)mentioning
confidence: 99%
“…In addition, we explored long-term data from the original UK survey instrument, and this instrument has now been modified. Satterthwaite and Roudsari ( 2020 ) explored the UK’s updated NSS instrument and found that, together with the perceived value of teaching quality, a new category of ‘learning opportunities’ was of significant importance. Parapadakis ( 2020 ) used related artificial intelligence approaches to explore NSS metrics from Computer Science courses and agreed generally with our predictors, whilst also highlighting differences in predictive factors between institutional typologies and institutional rankings.…”
Section: Discussionmentioning
confidence: 99%
“…The questions were the same for all the subjects involved in this experience: subjects 1, 3, 4, and 2, the latter only for the academic year 2020–21, from Table 1 . The Likert-type questions sought students’ assessment of the new teaching methodology of online practices, as well as their degree of satisfaction [ 41 , 42 ], while the multi-choice question was intended for students to point out what, in their opinions, were the advantages and disadvantages of the new methodology.…”
Section: Tools Used To Assess the New Methodologiesmentioning
confidence: 99%